Handbook of international rivalries, 1494-2010 - Thompson, William R. (Correlates of war series, 2012)
Examines numerous strategic rivalries-two states that view each other as threatening competitors to the point that they categorize their antagonists as enemies-that have been responsible for nearly 80 percent of the warfare of the past two hundred years.